Effect of the Magnetic Field on Simultaneous Photocatalytic Detoxification of Cr (Vi) and Phenol Red over Lafeo3/Znfe2o4 Heterostructures - Casagrande-Denardin, J; Radhalayam, D (Elsevier B.V., 2023)
LaFeO3/ZnFe2O4 (LFO/ZFO) p-n heterostructures were prepared by hydrothermal method and employed in the reduction of heavy metal Cr (VI) and degradation of organic pollutant phenol red (PR) from contaminated water in the absence and presence of external magnetic field (MF) under visible light irradiation. The LFO/ZFO displayed notable catalytic activity in the presence of the MF for treating the Cr (VI) and PR single pollutants (SP). Especially, the catalyst showed superior performance to detoxify the pollutants from Cr (VI)-PR mixed pollutants (MP) solution at 0.4 T of MF, i.e., 97.1 % Cr (VI) and 99.8 % PR degraded simultaneously. © 2022 Elsevier B.V.